2020
DOI: 10.21203/rs.3.rs-125526/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effects of Interval Training on Peripheral Brain Derived Neurotrophic Factor (BDNF) In Young Adults: A Systematic Review and Meta-Analysis

Abstract: The aim of the current meta-analysis was to determine the effects of acute and chronic interval training (IT) on peripheral BDNF concentrations in healthy young adults. A literature search was performed using six databases until February 2020. The TESTEX scale was used to assess the quality of studies. Effect sizes (ES) were computed and two-tailed α values <0 .05 and non-overlapping 95% confidence intervals (95% CI) were considered statistically significant. Heterogeneity, inconsistency (I2), and small-stu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Most studies examining the effect of exercise on cognitive function focused primarily on continuous forms of exercise such as running or cycling at a constant intensity (low, moderate, and/or high). The number of studies using an intermittent exercise (IE) protocol is limited [33], although acute HIIE protocols tend to increase concentrations of certain extracellular neurochemicals more significantly than low-intensity acute exercise protocols in healthy young adults [31,34,35] and lateand middle-aged older adults [36]. In a prospective randomized controlled trial, Winter et al [37] demonstrated that a HIIE protocol (2 × 3 min sprints) had greater benefits for cognition (vocabulary learning; exercise accelerates learning and improves long-term retention of learned material) than moderate-intensity exercise (40 min running) or a sedentary control condition in healthy male sports students.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies examining the effect of exercise on cognitive function focused primarily on continuous forms of exercise such as running or cycling at a constant intensity (low, moderate, and/or high). The number of studies using an intermittent exercise (IE) protocol is limited [33], although acute HIIE protocols tend to increase concentrations of certain extracellular neurochemicals more significantly than low-intensity acute exercise protocols in healthy young adults [31,34,35] and lateand middle-aged older adults [36]. In a prospective randomized controlled trial, Winter et al [37] demonstrated that a HIIE protocol (2 × 3 min sprints) had greater benefits for cognition (vocabulary learning; exercise accelerates learning and improves long-term retention of learned material) than moderate-intensity exercise (40 min running) or a sedentary control condition in healthy male sports students.…”
Section: Introductionmentioning
confidence: 99%
“…It plays a role in the development and growth of neurons, memory processes, apoptosis, neurogenesis, and neuroregeneration [ 19 ]. It belongs to the family of neurotrophins (NTs), which are polypeptide growth factors [ 20 ]. Apart from BDNF, these include neurotrophin-3 (NT-3), NT-4, NT-7, and glial cell-derived neurotrophic factor, which are produced in the brain and other tissues [ 21 ].…”
Section: Introductionmentioning
confidence: 99%